Fabricate Wavy Micro/Nano Fiber via Auxiliary Electrodes - Zhu, Ziming (2016)
Wavy micro/nano fiber is a common phenomenon in traditional electrospinning caused by bending instability. However, using bending instability to fabricate wavy fibers is hard to control the wavelength and amplitude of the wavy fibers. Auxiliary electrodes were developed to control the morphology of the wavy fibers in this paper, when a 4 wt% Poly(ethylene oxide)(PEO) solution was electrospun at 1KV applied voltage in near-field electrospinning, and the collector at relatively low speed, AC current power supplied to auxiliary electrodes, and the amplitude of wavy was increased as increasing the AC current power voltage supplied to the auxiliary electrodes, and the frequencies of the wavy fibers was the same as the frequencies of the AC current power. Therefore, AC current power supplied to auxiliary electrodes can be used to control wavy fibers fabrication.